Olfactory dysfunction as potential biomarker in neurodegenerative diseases: a narrative review - De Cleene, Nicolas; Schwarzová, Katarína; Labrecque, Samuel; Cerejo, Clancy; Djamshidian, Atbin; Seppi, Klaus; Heim, Beatrice (Frontiers in Neuroscience, 2025)
Neurodegenerative diseases represent a group of disorders characterized by progressive degeneration of neurons in the central nervous system, leading to a range of cognitive, motor, and sensory impairments. In recent years, there has been growing interest in the association between neurodegenerative diseases and olfactory dysfunction (OD). Characterized by a decline in the ability to detect or identify odors, OD has been observed in various conditions, including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), and Amyotrophic Lateral Sclerosis (ALS). This phenomenon often precedes the onset of other clinical symptoms, suggesting its potential utility as an early marker or prodromal symptom of neurodegenerative diseases. This review provides a vast literature overview on the current knowledge of OD in PD, AD, ALS, and HD in order to evaluate its potential as a biomarker, particularly in the early and prodromal stages of these diseases. We summarize the most common methods used to measure olfactory function and delve into neuropathological correlations and the alterations in neurotransmitter systems associated with OD in those neurodegenerative diseases, including differences in genetic variants if applicable, and cater to current pitfalls and shortcomings in the research.